2005
DOI: 10.1289/ehp.7783
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Sustained Exposure to the Widely Used Herbicide Atrazine: Altered Function and Loss of Neurons in Brain Monoamine Systems

Abstract: The widespread use of atrazine (ATR) and its persistence in the environment have resulted in documented human exposure. Alterations in hypothalamic catecholamines have been suggested as the mechanistic basis of the toxicity of ATR to hormonal systems in females and the reproductive tract in males. Because multiple catecholamine systems are present in the brain, however, ATR could have far broader effects than are currently understood. Catecholaminergic systems such as the two major long-length dopaminergic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 58 publications
3
60
0
Order By: Relevance
“…Roundup), alachlor, the bipyridyl paraquat and atrazine. Paraquat is the only herbicide substantially investigated in relation to PD, although there have been studies on the ability of atrazine to disrupt dopamine homeostasis at high concentrations [20]. A recent case-control study reported that herbicide exposure increased the risk of PD [21].…”
Section: Herbicidesmentioning
confidence: 99%
“…Roundup), alachlor, the bipyridyl paraquat and atrazine. Paraquat is the only herbicide substantially investigated in relation to PD, although there have been studies on the ability of atrazine to disrupt dopamine homeostasis at high concentrations [20]. A recent case-control study reported that herbicide exposure increased the risk of PD [21].…”
Section: Herbicidesmentioning
confidence: 99%
“…Thus, two separate studies found that ATR exposure decreased striatal dopamine (DA) levels and caused a loss of tyrosine hydroxylase (TH)-positive dopaminergic neurons in both the substantia nigra parts compacta (SNpc) and the ventral tegmental area (VTA) in rats (Rodriguez et al, 2005) and mice (Coban and Filipov, 2007). In addition, our laboratory found that in vitro exposure to ATR decreased the tissue levels of DA in striatal slices while media levels of DA and its turnover [(DOPAC + HVA)/DA] ratio were increased.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the toxic effects of atrazine exposure has revealed atrazine to be directly disruptive to the central nervous system, the endocrine system and the immune system (Cooper et al 1999; Rodriguez et al 2005; Sanderson et al 2001). Mencoboni et al 1992 found that acute intraperitoneal exposure to atrazine reduced hematopoietic progenitors for a short period.…”
mentioning
confidence: 99%